Frailty and cardiovascular outcomes in the National Health and Aging Trends Study. (29th July 2021) - Damluji, Abdulla A; Chung, Shang-En; Xue, Qian-Li; Hasan, Rani K; Moscucci, Mauro; Forman, Daniel E; Bandeen-Roche, Karen; Batchelor, Wayne; Walston, Jeremy D; Resar, Jon R; Gerstenblith, Gary
Abstract: Aims: Physical frailty is a commonly encountered geriatric syndrome among older adults without coronary heart disease (CHD). The impact of frailty on the incidence of long-term cardiovascular outcomes is not known.We aimed to evaluate the long-term association of frailty, measured by the Fried frailty phenotype, with all-cause-mortality and MACE among older adults without a history of CHD at baseline in the National Health and Aging Trends Study. Methods and Results: We used the National Health and Aging Trends Study, a prospective cohort study linked to a Medicare sample. Participants with a prior history of CHD were excluded. Frailty was measured during the baseline visit using the Fried physical frailty phenotype. Cardiovascular outcomes were assessed during a 6-year follow-up. Of the 4656 study participants, 3259 (70%) had no history of CHD 1 year prior to their baseline visit. Compared to those without frailty, subjects with frailty were older (mean age 82.1 vs. 75.1 years, P  <   0.001), more likely to be female (68.3% vs. 54.9%, P  <   0.001), and belong to an ethnic minority. The prevalence of hypertension, falls, disability, anxiety/depression, and multimorbidity was much higher in the frail and pre-frail than the non-frail participants. In a Cox time-to-event multivariable model and during 6-year follow-up, the incidences of death and of each individual cardiovascular outcomes were all significantly higher in the frail than in the non-frail patients including major adverse cardiovascular event (MACE) [hazard ratio (HR) 1.77, 95% confidence interval (CI) 1.53, 2.06], death (HR 2.70, 95% CI 2.16, 3.38), acute myocardial infarction (HR 1.95, 95% CI 1.31, 2.90), stroke (HR 1.71, 95% CI 1.34, 2.17), peripheral vascular disease (HR 1.80, 95% CI 1.44, 2.27), and coronary artery disease (HR 1.35, 95% CI 1.11, 1.65). Conclusion: In patients without CHD, frailty is a risk factor for the development of MACEs. Efforts to identify frailty in patients without CHD and interventions to limit or reverse frailty status are needed and, if successful, may limit subsequent adverse cardiovascular events. Graphical abstract: